DAMPIT ROBUSTA COFFEE EFFECT ON THE CREATININE KINASE LEVELS AND MUSCLE PAIN SCALES AMONG SPORT ENTHUSIAST - Salamy, M. Fath Alhaqqi Sanis; Qorib, Mohammad Fathul; Herawati, Lilik; Darmawan, Rizky; Mujahiddin, M. Izzul; Salamun, Salamun; Salamy, Ahmed Zaiyan Nahel; Salamy, Achmad Yarziq Mubarak Salis; Mohamed, Moh Nahar Azmi; Ramadhan, Ain Darojah Siddiq Ramadhan (Folia Medica Indonesiana, 2025)
Excessive eccentric exercise often results in muscle injury, reflected by elevated serum creatine kinase (CK) levels and delayed onset muscle soreness (DOMS). In Indonesia, coffee consumption after exercise has increased, with Dampit Robusta Coffee (DRC)—a local variety rich in caffeine and antioxidants considered a potential aid for recovery. This study evaluated the effect of DRC consumption on biomarkers of muscle damage and perceived soreness. A single-blind randomized controlled trial was conducted on 20 healthy untrained men aged 20–25 years, allocated into treatment (n = 10) and control (n = 10) groups. The treatment group consumed brewed DRC (≈200 mg caffeine/day) for five consecutive days, while the control group received placebo (coffee-flavored water). All participants performed a modified YMCA step test as an eccentric exercise protocol. Serum CK levels were measured at 2 and 24 hours post-exercise, and muscle soreness was assessed using a visual analogue scale (VAS). At both 2 and 24 hours, mean CK levels were lower in the DRC group compared with control, but differences were not significant (p > 0.05). However, analysis of CK change (ΔCK) showed a significant between-group difference, with CK decreasing in the DRC group but increasing in the control group (p = 0.031). VAS scores decreased significantly over time within both groups (p = 0.05), but between-group differences remained nonsignificant (p > 0.05). In conclusion, DRC consumption attenuated CK elevation after eccentric exercise, suggesting a protective effect against muscle injury, although its effect on soreness was inconclusive. Further studies with larger and more diverse samples are needed.